Main catch, bycatch, discard catch of set lift net fisheries with Light Emitting Diode (LED) as light attractor in marine coastal waters of Pangkep, Makassar Strait, Indonesia. Issue 1 (May 2021) - Musbir; Kurnia, Muhammad; Sudirman
Abstract: Application of light emitting diode (LED) is considered to energy saving and increased catches in lift net fisheries. Set lift net fisheries in marine coastal waters of Pangkep used compact fluorescent lamp (CFL) but this lamps consumed high energy and fuels. Application of light emitting diode (LED) is considered to energy saving and increased catches in lift net fisheries. The experimental fishing trial was conducted on 22 July-25 August 2020 in marine coastal waters of Pangkep, Makassar Strait, Indonesia. The study using 1 units of set lift net with LED as light attractor. The result of study show that The fishes catch consist of main catch 149.21 kg (67.73 %), by catch 37.28 kg (16.93 %), and discard catch 43.76 kg (19.86 %).